Gambaran Konflik Intrapersonal Perawat Scoping Review - Wijaya, Indra; Dwiantoro, Luky; Dwidiyanti, Meidiana (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Intrapersonal conflict is a condition where an individual has two desires that cannot be fulfilled simultaneously. This research aims to identify the description of intrapersonal conflict among nurses. The study design uses a scoping review method. Articles were identified using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) method. Inclusion criteria for this review article include articles in English or Indonesian, original articles, and articles that use quantitative, qualitative, and mixed research methods published within the last 5 years. A search of articles in this review yielded 819 articles, and the review identified 4 articles that met the inclusion criteria and were subsequently analyzed. The results of the analysis indicate the description of intrapersonal conflict among nurses, namely: (1) Career-related conflicts, hindered by further study; (2) Family-related conflicts. Nurses want to contribute to the family's economy but their partner asks them to take care of the children and the house; (3) Work-family life conflicts or sleep duration; (4) Religion-related conflicts, with an example of a Muslim nurse newly employed at a hospital but facing a mandatory rule to remove the hijab. The conclusion of this review article shows various descriptions of intrapersonal conflict among nurses and suggests that research be conducted to reduce or manage these conflicts.